Criticism of The Palestine-Israel Conflict in The Novel “The Seven Good Years” Perspective Alan Swingewood - Muhammad Hayyi' Lana Alkhan; Roma Ulinnuha (CMES (Center of Middle Eastern Studies), 2022)
The Israeli-Palestinian conflict is extremely complicated, which involves various aspects of life. The root of the main problem is undoubtedly political issues; building and defending the state and nation in each of the warring parties. This conflict reaps many diverse opinions among observers, academics, intellectuals and writers. One of the writers who has been critical of his work is Etgar Keret. This study seeks to look deeper into how social criticism is carried out by an Israeli writer on the Israeli-Palestinian conflict in the novel "The Seven Good Years" which uses Alan Swingewood's perspective. This type of research is qualitative research. The study reveals Keret’s the novel "The Seven Good Years" conveyed a critical attitude towards the government of his own country. Keret opposes the Israeli occupation of Palestine, as well as conveys messages of peace. Social criticism of the conflict between Israel and Palestine in this novel includes criticism of the government, pressure from Israeli citizens, and hopes for peace.